THE CASE OF BUSINESS SIMULATIONS IN HIGHER EDUCATION IN SOUTH AFRICA - HOUGH, JOHAN (South African Journal of Higher Education, 2016)
The purpose of this article is to describe a case study for the use of on-line business simulation at Stellenbosch University. The discussion takes into account Information Communication Technology (ICT) developments in Africa and the University’s existing technological infrastructure. The paper identifies ICT practices in various global academic disciplines and highlights the purpose, advantages and disadvantages of business simulations. The case of on-line simulation in a post-graduate business strategy course is described and the results of students’ feedback are analysed. The paper concludes with the challenge to find the optimal blend of practical higher education learn¬ing experiences that can be enhanced by the most favourable and feasible mixture of ICT applications under certain limited conditions.